Indícios de interlíngua em sinalizantes ouvintes da Libras - Pinheiro, Camila Barbosa (Universidade Federal do Tocantins, 2021)
Within the process of acquiring and learning a language other than the mother tongue, there are linguistic phenomena that happen to the learner, who is not aware of it, but makes use of it. The purpose of this research is to discuss the process of acquiring Libras as L2 by hearing learners and to demonstrate probable traits that point to interlanguage as support in the production of L1 (first language) to L2 (second language), in the signing of hearing learners of Libras. Four videos from the YouTube platform were analyzed, in which there are signing hearing learners in the learning phase and some already fluent in LIBRAS. It was noticed the presence of interlanguage at the syntactic level, whose linguistic structure is similar to the Portuguese language. In that sense, it is important that the learner and the teacher are aware of the risk of the interlanguage becoming, over the years, a fossilized structure, which can be difficult to modify.